Successful retrograde recanalization of acute right dominant vertebral artery occlusion through the left posterior communicating artery in a patient with acute vertebrobasilar ischemic stroke - Anton A. Khilchuk, MD; Maksim V. Agarkov, MD; Sergey V. Vlasenko, MD, PhD; Sergey G. Scherbak, MD, Doctor of Sciences, professor; Andrey M. Sarana, MD, PhD; Svetlana V. Lebedeva, MD (Radiology Case Reports, 2018)
Advanced endovascular technology and techniques allow interventional radiologists to utilize novel ways of basilar artery recanalization in the setting of acute ischemic stroke, especially when routine approaches are not eligible. Several authors described nonstandard revascularization techniques in acute ischemic strokes due to basilar and middle cerebral arteries occlusions with full technical and clinical success. In this report, we present retrograde right vertebral artery recanalization using left posterior communicating artery for subsequent anterograde balloon angioplasty and stenting of a right vertebral artery ostium followed by full vertebrobasilar blood flow restoration. The case underscores the complexity of arterial thrombotic events, the beneficial role of endovascular intervention in vertebral occlusions and the necessity of prospective studies that identify optimal methods of treating vertebrobasilar stroke due to large vessel occlusions and their effectiveness and safety. Keywords: Ischemic, Stroke, Vertebral, Basilar, Occlusion, Recanalization